Identifier syntax and mnemonics in programming languages - Grigaliūnas, Mikas; Grigas, Gintautas (Lietuvos matematikos rinkinys, 2000)
The main attention in the paper is paid to the set of symbols, which can be used in identifiers. Modern computers uses 8 bit coding, and many programming languages does so. But only few of them (Logo, Component Pascal) takes all advantages of 8 bit coding and allows to use all letters of alphabet in identifiers. Proffesional languages such as Pascal and C have restrictions for a symbol set in identifiers. These restrictions comes back from 7 or even 6 bit coding. The recent standards of programming languages allows to extend symbol set. Such kind of extension – interface between IbrboPascal and MS Word, which allows to use Lithuanian and Latvian letters in Pascal program identifiers, is presented in this paper. Some languages (Ada95, Java) already uses Unicode. The sets of symbols for identifiers in these languages are defined in different ways. Unicode itself provides syntax rules for identifiers, in order to ensure uniform treatment of identifiers.